Participatory Management of Bontang Mangrove Park East Kalimantan, Indonesia - Nur Patria Kurniawan; Edi Purwanto; Zahrotun Nisa’a Asih Daryono (Universitas Panji Sakti, 2022)
Researchers found several land-use problems arise in East Kalimantan. The un-managed wildland was studied to develop its potential. The existing potential is to build the Bontang Mangrove Park ecotourism. The ecotourism management of Bontang Mangrove Park stillcan be optimized, thus this study aims to describe the management implementation of the Bontang Mangrove Park development for the people of East Kalimantan, including aspects of planning (planning), organizing (organizing), activities (acting) and evaluation or control This research was conducted in a year in 2021 for an year, but the data were taken from 2018 – 2021. This research is quantitative and descriptive. The population used for this study were all employees and facilitators at Bontang Mangrove Park. The sampling technique in this study used a purposive sampling technique, consisting of employees, core facilitators, and the community. The data analysis technique is used descriptively as outlined in the form of a PAOC description. Based on the results of the study, it is known that the management of Bontang Mangrove Park in terms of the management process is good, the organization is good, and the implementation categorized as very good.